Heparin and Insulin for Hypertriglyceridemia-Induced Pancreatitis: Case Report - Deepika Jain; John Zimmerschied (The Scientific World Journal)
Hypertriglyceridemia is the etiology of acute nonbiliary pancreatitis in up to 3% of patients. Along with the supportive treatment of acute pancreatitis, treating the precipitating cause is important as well. There have been reports where heparin and insulin have been used for acute reduction of triglycerides, although there are no established guidelines for efficacy of these modalities. Heparin and insulin decrease triglycerides by stimulating lipoprotein lipase activity, which degrades triglycerides into fatty acids and glycerol. We present a case where a 54-year-old male presented with hypertriglyceridemia-induced acute pancreatitis. The serum triglyceride level was 10,320 mg/dl (normal: 0–15 mg/dl) at the time of admission. We started the patient on intravenous insulin and heparin infusion, and within 24 h of induction of treatment, the levels decreased by 50% to 5407 mg/dl. Thus, heparin and insulin can be considered a safe treatment modality for rapidly reducing triglyceride levels.